The challenges and future perspective of Kenaf Wo-ven reinforcement in thermoset polymer composites in Malaysia: a review - Lee, Ching Hao; Abdan, Khalina; Norizan, Mohd Nurazzi; Abdullah, Norli; M., M. Harussani; Shafi, Ayu Rafiqah; Alias, Aisyah Humaira; Ramli, Natasha (MDPI AG, 2021)
In this review, the challenges faced by woven kenaf thermoset polymer composites in Malaysia were addressed with respect to three major aspects: woven kenaf reinforcement quality, Malaysian citizen awareness of woven kenaf thermoset composite products, and government supports. Kenaf plantations were introduced in Malaysia in the last two decades, but have generally not produced much kenaf composite product that has been widely accepted by the public. However, woven kenaf fiber enhances the thermoset composites to a similar degree or better than other natural fibers, especially with respect to impact resistance. Woven kenaf composites have been applied in automotive structural studies in Malaysia, yet they are still far from commercialization. Hence, this review discusses the kenaf fiber woven in Malaysia, thermoset and bio-based thermoset polymers, thermoset composite processing methods and, most importantly, the challenges faced in Malaysia. This review sets guidelines, provides an overview, and shares knowledge as to the potential challenges currently faced by woven kenaf reinforcements in thermoset polymer composites, allowing researchers to shift their interests and plans for conducting future studies on woven kenaf thermoset polymer composites.